Google meet menjadi media alternatif yang fleksibel dalam pembelajaran Maharah Kalam pada masa pandemi (covid-19) di UIN MALIKI malang - Naafiah, Lailatun; Mufidah, Nuril (Maliki Interdisciplinary Journal, 2024)
This study aims to explain the technical and stages of online learning during the Covid-19 pandemic by using Google Meet media in the Maharah Kalam course as well as explain how the advantages and disadvantages of lectures using Google Meet media in maharah kalam lectures during the Covid-19 pandemic at UIN Maulana Malik Ibrahim Malang. This research is descriptive qualitative where this research reveals the facts that occurred in the field where data collection was obtained by conducting observational activities carried out in class Bk at UIN Maulana Malik Ibrahim Malang. Data was also obtained from the results of interviews with 2nd semester students majoring in PBA for the 2021/2022 academic year who took part in maharah kalam courses in class Bk. And data in the form of documentation such as photos, and student attendance were obtained from maharah kalam lecture activities using Google Meet media. The results of this study revealed that the stages and technicalities of maharah kalam lectures use Google Meet media, namely, when before the lecture time begins, the lecturer first creates a Google Meet link which will later be shared by the lecturer to students through the Whatsapp group application. Furthermore, in the implementation of Maharah Kalam lectures themselves, lecturers use 3 types of online presentations, but what is often used is the type of learning Syncronous courses, and uses three methods in maharah kalam, namely mastery of mufrodat, insya’, and muhadatsah by utilizing the Sharescreen, Mute, Unmute features provided by Google Meet. Google Meet media itself has represented in-person meetings, where maharah kalam lectures that should need to be done directly but can run effectively by using this very accessible Google Meet media. The advantages of online learning using Google Meet media are: Making students who were originally passive in class become active, More flexible and can be done anywhere, Providing a learning experience from audio, video, text, to convey information, Access is very easy, Has a lot of learning support features, such as sharescreen, record, raisehand, Free download application. And the drawbacks are: Unstable signal, Disruption of focus caused by the surrounding environment that is not supportive, Many of the materials provided are difficult to understand, Many students underestimate because they are not monitored directly by the lecturer, Must always have a quota or wifi network that stays, There is no data saving feature.